Introduction to property theory the fundamental theorems - Ellerman, David P. (Policy research working papers / World Bank, 2001)
This paper inaugurates the mathematical treatment of property theory, proving the two fundamental theorems for the property system that correspond to the two fundamental theorems for the competitive price system.